2021
DOI: 10.3390/bioengineering8110181
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Electrodiagnosis of Carpal Tunnel Syndrome Using Machine Learning

Abstract: Recent literature has revealed a long discussion about the importance and necessity of nerve conduction studies in carpal tunnel syndrome management. The purpose of this study was to investigate the possibility of automatic detection, based on electrodiagnostic features, for the median nerve mononeuropathy and decision making about carpal tunnel syndrome. The study included 38 volunteers, examined prospectively. The purpose was to investigate the possibility of automatically detecting the median nerve mononeur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…We reported the maximum FR regardless of the site of flattening, yet that was at the level of proximal carpal tunnel at most of the cases. On the contrary, another study, showed significant difference in FR at the proximal carpal tunnel (2.2± 0.52 in the control group & 2.7 ± 0.9 in the patient group, p value < 0.0001) with 72.5 % & 65.6 % specificity using a of cut off value >2.4 (3) . With the use of the same cut off value, our study showed 60 % sensitivity & 90 % specificity (p value =0.091).…”
Section: Frmentioning
confidence: 84%
See 4 more Smart Citations
“…We reported the maximum FR regardless of the site of flattening, yet that was at the level of proximal carpal tunnel at most of the cases. On the contrary, another study, showed significant difference in FR at the proximal carpal tunnel (2.2± 0.52 in the control group & 2.7 ± 0.9 in the patient group, p value < 0.0001) with 72.5 % & 65.6 % specificity using a of cut off value >2.4 (3) . With the use of the same cut off value, our study showed 60 % sensitivity & 90 % specificity (p value =0.091).…”
Section: Frmentioning
confidence: 84%
“…These values are less than that suggested by other studies. For example, in another study, the sensitivity was 85 % with 100 % specificity using >15 mm 2 at pisiform bone as cut off value (3) . In another example the cut off value of CSA at pisiform bone was 14.4 mm 2 in another study, with sensitivity = 90 % (9) .…”
Section: Morphological Mri Parameters In Cts Diagnosis: Csamentioning
confidence: 97%
See 3 more Smart Citations